Climate Investment Opportunities in South Asia - International Finance Corporation (Washington, DC, 2018)
South Asia is home to three of the top five countries in terms of vulnerability to climate change globally.It thus urgently needs climate investment to enhance resilience and unlock opportunities for low carbon growth. The region is one of the fastest growing regions in the world; however, estimates suggest that climate impacts could reduce its annual gross domestic product by an average of 1.8 percent by 2050,rising to 8.8 percent by 2100.The good news is that the region has governments that are actively pursuing ambitious policies to address climate change. Moreover, its private sector is already investing in climate-smart sectors, developing new business models and technologies,building more resilient supply chains, and growing their operations in sustainable way.Countries of focus for this report have been identified based on IFC’soperational regional grouping for South Asia, which includes Bangladesh,Bhutan, India, the Maldives, Nepal, and Sri Lanka. All six of these countries have ratified the 2015 Paris Agreement and pledged to tackle climate change in support of it, as part of their ambitious long-term economic growth and sustainable development plans. Almost all the Nationally Determined Contributions (NDCs) across the region make some reference to the private sector’s role. Climate business activity in keysectors such as renewable energy, green buildings, and energy-efficiency has increased since the Paris Agreement, boosted by governments’ commitments to address climate change.